The new fern genus Calciphilopteris (Pteridaceae) - Yesilyurt, J. C.; Schneider, H. (Phytotaxa, 2013)
A new genus of Pteridaceae subfamily Cheilanthoideae is established for what has long been known as Doryopteris ludens. The newly erected genus is named Calciphilopteris in reference to its substrate specificity to limestone. Calciphilopteris can be found throughout Southeast Asia, from Indo-China to New Guinea and Australia. New combinations are established for the four known species (Calciphilopteris alleniae, C. ludens, C. papuana and C. wallichii). Calciphilopteris is characterized by having a horizontal rhizome, semi-clathrate scales, indumentum on the petiole and lamina usually with fibrils and/or semi- to non-clathrate scales, and sporangia with 32 echinate or cristate spores.